A NOVEL DESIGN OF FLOWER TYING MACHINE - Kuruvilla, Sincy Elezebeth; B N, Vasanth Kumar; C, Lakshmishree; Dhanraj, Molkire Vaishnavi; G M, Kavya (The journal of contemporary issues in business and government, 2021)
A prototype model of automated flower string machine is proposed to knot the flowers. In India’s rich culture flower garlands play a vital role. They are used for decorations and adorations of Gods, men and women. Garlanding of flower is a monotonous and time- consuming job. The flower string machine is conceptualized based on the working principle of sewing machine and added multiple kinematic mechanisms to drive the flower feeding and stringing. The flowers will be placed on the conveyor belt and based on process control technique; an innovative knotting mechanism will be used to string the flowers. It is also a customized machine for armless and loss of fingers community. Flower tying machine ensures perfect garlanding in an affordable cost. By this technique, the manual work can be reduced and flower vendors can utilize their time effectively.